(untitled) (Research, Society and Development, 2020)
COVID-19 is an emerging infectious disease that represents a significant threat to public health worldwide. That indicates the need for adherence to public policies with preventive, control, and rapid and accurate diagnosis measures as part of the measures to contain the pandemic’s advance. This study aimed to analyze the main laboratory findings of the respiratory syndrome caused by the new coronavirus SARS-CoV-2 through a narrative review of the literature. The coronavirus viral RNA detection technique has been described as the principal methodology used for clinical diagnosis. Among the laboratory findings, lymphocytopenia decreased hemoglobin and serum albumin values, increased lactate dehydrogenase (LDH) and C-Reactive Protein (CRP), increased erythrocyte sedimentation rate (ESR) were observed. D- dimer has been linked to poor prognosis in critically ill patients. In the current context, laboratory tests can contribute to the early identification of signs of severity and poor prognosis of the respiratory syndrome caused by the new SARS-CoV-2.